Exploratory and confirmatory molecular approaches to determine genetically modified status in different crops - Hanaa Abdel-Sadek Oraby (SpringerOpen, 2021)
Abstract Background One of the parameters required for the assessment of food and feed safety is detection and identification of genetically modified organisms. Legislation in some countries necessitates detection and quantification of modification in food and feed samples. Scientists have raised concern about safety of antibiotic resistance marker (ARM) genes used for transformation of crops intended for human and animal consumption. In the present work two molecular approaches have been adopted: one exploratory; for detection and quantification of ARM genes in tested plant samples and the other confirmatory; to determine the specificity/reliability of the obtained results. Results Results revealed that primers for neomycin phosphotransferase (nptII) and aminoglycoside 3″ adenyl-transferase (aadA) were amplified in the majority of the 36 DNA screened samples. Melting curve analysis using hygromycin phosphotransferase (aphIV) gene as target sequence for the fluorescent-based detection approach was performed to ensure reliability and specificity of this procedure and to confirm results obtained by using conventional polymerase chain reaction (PCR). Quantitative RT-PCR results and validation analysis followed, revealed that all of the tested DNA samples were not violating the European legislation for GMOs labeling (0.9%). Conclusions The results fully demonstrated the reproducibility, sensitivity/specificity of the adopted approaches for detection and quantification of even traces of GMO contents. Applying measurement uncertainty (MU) procedures presented in this work will help decision makers to ensure compliance with International Legislation and Regulations. This in its turn will facilitate and enhance trading with countries having compelling labeling regulations.